Implementation of Ex-Gratia Claim Payment in Insurance Agreement - Windiantina, Wiwin Wintarsih; Suparman, Eman; Ikhwansyah, Isis; Suryanti, Nyulistiowati (Richtmann Publishing, 2022)
This study aims to explain descriptively about the implementation of ex-gratia claims on life insurance agreements, how to pay and settle ex-gratia claims and ex-gratia claim terms. In the Life Insurance agreement, the insured party when experiencing an unexpected risk of obtaining its rights in the settlement of claims. The occurrence of rejection of claims on life insurance, becomes the cause of a lack of understanding of the actual articles and regulations must be understood before deciding to use insurance. In fact, not all losses suffered by the insured in the insurance agreement can be paid according to the agreement. It is caused by several factors that are considered to violate the principles of insurance and regulations that have been determined in the insurance agreement, resulting in the cancellation of the insurer pays its obligations to the insured or commonly called rejected claims. But customers sometimes still demand that the company pay, therefore the insurance company takes the initiative to pay claims rejected through Ex-gratia. But many people do not know about the ex-gratia claim. Some insurers take the initiative to pay ex-gratia rejected claims. Implementation of ex gratia claims can be done by negotiation, good faith from the insurer to the insured. Received: 15 October 2021 / Accepted: 30 November 2021 / Published: 5 January 2022